The influence of Kuala Lumpur Stock Exchange Composite Index (KLSE CI) on the performance of the equity index tracker fund (a case study of MBF equity) / Suryani Abdul Hamid - Abdul Hamid, Suryani (2002)
1959 is a memorable year in the history of the Malaysian Unit Trust Industry as it makes the first appearance of unit trust in Malaysia. The formative years of the industry (spanning 2 decades) were challenging due to lack of public awareness and interest in unit trust.